1990
DOI: 10.1152/jn.1990.63.5.1068
|View full text |Cite
|
Sign up to set email alerts
|

ATP-induced current in isolated outer hair cells of guinea pig cochlea

Abstract: 1. Electrical and pharmacologic properties of ATP-induced current in outer hair cells isolated from guinea pig cochlea were investigated in the whole-cell recording mode by the use of a conventional patch-clamp technique. 2. Under current-clamp conditions, rapid application of ATP depolarized the outer hair cells resulting in an increase in conductance. The ATP-induced response did not show any desensitization during a continuous application. 3. At a holding potential of -70 mV, the ATP-induced inward current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 0 publications
8
47
0
Order By: Relevance
“…These ion channels are non-selective for Na + and K + (Nakagawa et al 1990) and when facing the unique environment of the scala media, with its high K + concentration (approximately 150 mM), activation under normal conditions would result in K + influx with current outflow via basolateral K + channels causing a decline in EP. The pharmacology of the ATP-induced fall in EP supports this P2X receptor-mediated mechanism (Muñoz et al 1995(Muñoz et al , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…These ion channels are non-selective for Na + and K + (Nakagawa et al 1990) and when facing the unique environment of the scala media, with its high K + concentration (approximately 150 mM), activation under normal conditions would result in K + influx with current outflow via basolateral K + channels causing a decline in EP. The pharmacology of the ATP-induced fall in EP supports this P2X receptor-mediated mechanism (Muñoz et al 1995(Muñoz et al , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…The dissection procedure of the guinea pig OHCs was similar to that previously reported (Nakagawa et al 1990). Albino guinea pigs (weight 150-300 g) of either sex with good Preyer's reflexes were decapitated, and the temporal bones were removed.…”
Section: Isolation Of Ohcsmentioning
confidence: 99%
“…Studies have shown that extracellularly applied ATP can elicit changes in intracellular Ca2+ concentrations and transmembrane ion conductance in isolated hair cells (Ashmore and Ohmori, 1990;Nakagawa et al, 1990;Shigemoto and Ohmori, 1990;Dulon et al, 1991;Housley et al, , 1993aAshmore et al, 1993). These effects are consistent with a P, purinoceptor classification.…”
mentioning
confidence: 99%